Chapter Quando l'amore colpisce l'udito: La malia della voce di Carlo Gozzi fra Agustín Moreto e Thomas Corneille - Gutiérrez Carou, Javier (Studi e saggi, 2020)
In the preface to the edition of La malia della voce, Carlo Gozzi declares that the only source of his text is Lo que puede la aprehensión by Agustín Moreto, refusing any filiation with La charme de la voix by Thomas Corneille, a French adaptation of the same Spanish comedy, a statement that is astonishing if we take into account even the title of the Italian version, a literal translation of that from across the Alps. This essay studies the relationships between the three works in search of coincidences and divergences, textual and structural, which allow us to establish the real genetic relationship between the Italian text and the Spanish and French previous versions.